2008
DOI: 10.1002/adsc.200800387
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Asymmetric β‐Peroxidation of Nitroalkenes

Abstract: The first example of an asymmetric b-peroxidation of nitroalkenes is disclosed. The reaction is promoted by catalytic loadings of a commercially available diaryl-2-pyrrolidinemethanol derivative and tert-butyl hydroperoxide as the oxidant. A synthetically useful class of peroxides is obtained in good yield and enantioselectivity (up to 84% ee).Keywords: asymmetric catalysis; Michael addition; nitroalkenes; organocatalysis; peroxides Catalytic asymmetric conjugate additions are fundamental reactions in organic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…6 In fact, this type of reactions still represent one of the most challenging cases of conjugate addition of heteroatom-centered nucleophiles under organocatalytic activation because, in addition to reversibility issues, the typical oxygen-centered pronucleophiles, such as alcohols or carboxylic acids, typically show very poor reactivity towards Michael acceptors and normally undergo competitive 1,2-addition. Consequently, the reported examples of organocatalytic and enantioselective conjugate addition of oxygen pronucleophiles are limited to the use of oximes, 7 phenols, 8 enols, 9 alkoxyboronates, 10 hydroxylamines, 11 or peroxides 12 under iminium or H-bonding activation. 13 Organocatalytic cascade processes initiated by conjugate addition of O -nucleophiles have been mainly focused on the epoxidation of α,β-unsaturated carbonyls with peroxides 14 and some limited examples of conjugate addition followed by aldol, 15 Mannich, 16 Henry, 17 α-amination 18 and α-fluorination 19 have also been published.…”
Section: Introductionmentioning
confidence: 99%
“…6 In fact, this type of reactions still represent one of the most challenging cases of conjugate addition of heteroatom-centered nucleophiles under organocatalytic activation because, in addition to reversibility issues, the typical oxygen-centered pronucleophiles, such as alcohols or carboxylic acids, typically show very poor reactivity towards Michael acceptors and normally undergo competitive 1,2-addition. Consequently, the reported examples of organocatalytic and enantioselective conjugate addition of oxygen pronucleophiles are limited to the use of oximes, 7 phenols, 8 enols, 9 alkoxyboronates, 10 hydroxylamines, 11 or peroxides 12 under iminium or H-bonding activation. 13 Organocatalytic cascade processes initiated by conjugate addition of O -nucleophiles have been mainly focused on the epoxidation of α,β-unsaturated carbonyls with peroxides 14 and some limited examples of conjugate addition followed by aldol, 15 Mannich, 16 Henry, 17 α-amination 18 and α-fluorination 19 have also been published.…”
Section: Introductionmentioning
confidence: 99%
“…Peroxides 6 are known compounds, their analytical data were identical to those reported in the literature. 9 Enantiomeric excess was determined by chiral HPLC using Daicel Chiralcel OD-H and Daicel Chiralpak AS-H columns. 9…”
Section: Epoxidation Of Trans-ab-enones; General Proceduresmentioning
confidence: 99%
“…In this context, we recently found that commercially or readily accessible diarylprolinols 1 and primary b-amino alcohols 2 catalyze the epoxidation of a,b-enones in the presence of tert-butyl hydroperoxide (TBHP) as the oxygen source. 8 Moreover, this simple catalytic system could be applied to realize an unprecedentedly reported asymmetric b-peroxidation of nitroalkenes 9 (Scheme 1). Epoxides 4 and peroxides 6 could be obtained in good to high yield and enantioselectivity (70-92% ee).…”
mentioning
confidence: 99%
“…Recently, we disclosed that α,α‐diaryl‐ L ‐prolinols promote asymmetric Michael additions, such as the epoxidation of α,β‐enones,13 the β‐peroxidation of nitroalkenes14 and the malonate ester addition to nitroalkenes15 with high to moderate levels of enantioselectivity. We proposed a dual mode of activation of the nucleophile and the electrophile provided by the amine and the hydroxy groups of these organocatalysts, respectively.…”
Section: Introductionmentioning
confidence: 99%